2006
DOI: 10.1016/j.jacc.2006.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adiponectin Levels Are Associated With Coronary Lesion Complexity in Men With Coronary Artery Disease

Abstract: Plasma adiponectin levels are significantly associated with coronary lesion complexity in men with CAD. Low adiponectin levels may contribute to coronary plaque vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(91 citation statements)
references
References 41 publications
6
77
0
8
Order By: Relevance
“…Furthermore, in a study of Japanese men with CAD, patients with acute coronary syndrome had lower adiponectin levels than stable CAD patients, whereas patients with multiple complex lesions had significantly lower adiponectin levels than those with solitary complex lesions. 13 Thus, low adiponectin levels may be related to vulnerability to coronary atherosclerosis, which was also confirmed by the results of the present study. An important new finding of the present study is that adiponectin levels were monitored in a cohort and cardiovascular events were assessed prospectively.In our study, the low adiponectin level predicted cardiovascular events but not cerebrovascular events.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, in a study of Japanese men with CAD, patients with acute coronary syndrome had lower adiponectin levels than stable CAD patients, whereas patients with multiple complex lesions had significantly lower adiponectin levels than those with solitary complex lesions. 13 Thus, low adiponectin levels may be related to vulnerability to coronary atherosclerosis, which was also confirmed by the results of the present study. An important new finding of the present study is that adiponectin levels were monitored in a cohort and cardiovascular events were assessed prospectively.In our study, the low adiponectin level predicted cardiovascular events but not cerebrovascular events.…”
Section: Discussionsupporting
confidence: 89%
“…In other studies, hypoadiponectinemia was observed to correlate with the prevalence or extent of CAD (11,12) and to serve as a risk factor for coronary heart disease (13,14). The aim of the present study, therefore, was to explore the relationship between serum adiponectin concentrations and the presence of the metabolic syndrome among patients with CAD.…”
Section: Adiponectin An Adipokine Now Recognized As a Key Regulator mentioning
confidence: 84%
“…Clinical studies showed that patients with CAD or immediately after acute coronary syndrome had decreased plasma adiponectin concentrations 8,28) . Otsuka et al indicated that plasma adiponectin levels were significantly associated with coronary lesion complexity in men with CAD, and suggested that hypoadiponectinemia may contribute to coronary plaque vulnerability 9) . Pischon and colleagues reported that high plasma adiponectin concentrations were associated with a lower risk of myocardial infarction among men without previous cardiovascular disease 15) ; however, Sattar and coworkers suggested that the relationship between adiponectin levels and CHD risk is comparatively moderate and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with coronary artery disease (CAD) were shown to have decreased plasma adiponectin concentrations 8) . In addition, plasma adiponectin levels are significantly associated with the complexity of coronary lesions in men with CAD, suggesting that hypoadiponectinemia may contribute to coronary plaque vulnerability 9) ; however, there is uncertainty about the association between circulating concentrations of adiponectin and coronary heart disease (CHD) risk in patients after acute myocardial infarction (AMI).…”
Section: Introductionmentioning
confidence: 99%